2021
DOI: 10.1146/annurev-micro-041321-042402
|View full text |Cite
|
Sign up to set email alerts
|

Causative Microbes in Host-Microbiome Interactions

Abstract: Despite identification of numerous associations between microbiomes and diseases, the complexity of the human microbiome has hindered identification of individual species and strains that are causative in host phenotype or disease. Uncovering causative microbes is vital to fully understand disease processes and to harness the potential therapeutic benefits of microbiota manipulation. Developments in sequencing technology, animal models, and bacterial culturing have facilitated the discovery of specific microbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 154 publications
0
3
0
Order By: Relevance
“…Efforts to understand how bacterial species or strains within the microbiome contribute to a mucosal immune response have largely focused on the adaptive immune system (Britton et al, 2020;Britton and Faith, 2021;Geva-Zatorsky et al, 2017;Ivanov et al, 2009;Mazmanian et al, 2005;Viladomiu et al, 2017;Yang et al, 2020). Historically, the signaling pathways fundamental to our understanding of innate immunity have been elucidated using pathogen models.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to understand how bacterial species or strains within the microbiome contribute to a mucosal immune response have largely focused on the adaptive immune system (Britton et al, 2020;Britton and Faith, 2021;Geva-Zatorsky et al, 2017;Ivanov et al, 2009;Mazmanian et al, 2005;Viladomiu et al, 2017;Yang et al, 2020). Historically, the signaling pathways fundamental to our understanding of innate immunity have been elucidated using pathogen models.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal macrophages play vital roles in maintaining gut homeostasis, regulating inflammation, and particularly in promoting the resolution of inflammation (Lavelle and Sokol, 2020;Na et al, 2019), which has been considered as a novel potential target for controlling intestinal pro-inflammatory disorders. It has been reported that probiotics-derived metabolites, such as bacteriocins, antimicrobial compounds, short-chain fatty acids, and tryptophan/indole derivatives, can mediate the beneficial effects of probiotics on the host health by interacting with the host gastrointestinal immune cells and gut residents (Britton and Faith, 2021;Sanders et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Besides several limited examples, we do not understand the molecular mechanisms and the microbial signals that lead to specific T cell responses in the gut (Ansaldo et al, 2019; Ivanov et al, 2009; Nagashima et al, 2022; Tan et al, 2016). Efforts to parse microbiota-dependent immune phenotypes have either used time-intensive methods or relied upon trial-and-error in vivo experimentation (Atarashi et al, 2015, 2011; Britton et al, 2020; Britton and Faith, 2021; Faith et al, 2014; Geva-Zatorsky et al, 2017; Surana and Kasper, 2017; Viladomiu et al, 2017). Furthermore, given the broad compositional differences within disease-associated human microbiotas (Contijoch et al, 2019; Gevers et al, 2014), it is not known if the recognition of microbiota-derived strains by the host immune system depends on the host environment, such as the presence or absence of inflammation.…”
Section: Introductionmentioning
confidence: 99%